2014
DOI: 10.1021/jz402493b
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics of Hydrated Phospholipid Surfaces Probed by Ultrafast 2D Spectroscopy of Phosphate Vibrations

Abstract: The properties of biomembranes depend in a decisive way on interactions of phospholipids with hydrating water molecules. To map structural dynamics of a phospholipid-water interface on the length and time scale of molecular motions, we introduce the phospholipid symmetric and asymmetric phosphate stretch vibrations as probes of interfacial hydrogen bonds and electrostatic interactions. The first two-dimensional infrared spectra of such modes and a line shape analysis by density matrix theory reveal two distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 33 publications
3
58
1
Order By: Relevance
“…26 The phospholipid-water interface is subject to very strong electrostatic fields originating from the phosphate-choline dipole moments of approximately 20 D. Such fields have a strong in-plane component at the interface and orient the much smaller water dipoles. Molecular dynamics simulations found that water molecules connect different phospholipids and that the lifetime of these water bridges is up to 50 ps.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…26 The phospholipid-water interface is subject to very strong electrostatic fields originating from the phosphate-choline dipole moments of approximately 20 D. Such fields have a strong in-plane component at the interface and orient the much smaller water dipoles. Molecular dynamics simulations found that water molecules connect different phospholipids and that the lifetime of these water bridges is up to 50 ps.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Interestingly, there is a universal 300 fs lifetime of ν AS (PO − 2 ) that is independent of the studied system and the water content around the phosphate groups. Such a behavior suggests a common relaxation mechanism that involves low-frequency vibrations of the PO 4 tetrahedron.…”
Section: Vibrational Lifetimesmentioning
confidence: 93%
See 3 more Smart Citations